National Steinbeck Center display - Arthur Landy (artist):::Creator::::::::::::
National Steinbeck Center (NSC, 1 Main Street) display of untitled painting showing field workers at work. Painting by Arthur Landy (1904-1977). Landy worked extensively in movies from 1947-1967, mostly as a set decorator and background animator. From a series of publicity shots. Color bars at bottom of scan are part of original slide. Slide only.